A Century of Brain Regeneration Phenomena and Neuromorphological Research Advances, 1890s–1990s—Examining the Practical Implications of Theory Dynamics in Modern Biomedicine - Stahnisch, Frank W. (Frontiers in Cell and Developmental Biology, 2022)
The modern thesis regarding the “structural plastic” properties of the brain, as reactions to injuries, to tissue damage, and to degenerative cell apoptosis, can hardly be seen as expendable in clinical neurology and its allied disciplines (incl. internal medicine, psychiatry, neurosurgery, radiology, etc.). It extends for instance to wider research areas of clinical physiology and neuropsychology which almost one hundred years ago were described as a critically important area for both the brain sciences and psychology alike. Yet the mounting evidence concerning the range of structural neuroplastic phenomena beyond the significant early three years of childhood has shown that there is a progressive building up and refining of neural circuits, in order to adapt to the surrounding environment. This review essay explores the history behind multiple biological phenomena that were studied and became theoretically connected with the thesis of brain regeneration phenomena from Santiago Ramón y Cajal’s pioneering work since the 1890s to the beginning of the American “Decade of the Brain” in the early 1990s. It particularly analyzes the neuroanatomical perspectives on the adaptive capacities of the Central Nervous System (CNS) or such model-like phenomena in the Peripheral Nervous System (PNS) that were seen as displaying major central regenerative processes. Structural plastic phenomena have assumed large implications for the burgeoning field of regenerative or restorative medicine, while they also pose significant epistemological challenges for the related experimental and theoretical research endeavors. After an exploration of early historical research precursors that investigated brain regeneration phenomena in non-vertebrates at the beginning of the twentieth century, such as in light microscopic studies and later the electron microscopic findings that substantiated the presence of structural neuroplastic phenomena in higher cortical substrates. Furthermore, experimental physiological research in hippocampal in vivo models of regeneration further confirmed and corroborated clinical physiological views, according to which “structural plasticity” could be interpreted as a positive regenerative CNS response to brain damage and degeneration. Yet the underlying neuroanatomical mechanisms remained to be established and the respective pathway effects needed to be conveyed through the discovery of neural stem cells in the brains of adult mammals in the early 1990s.